2006
DOI: 10.1890/1051-0761(2006)016[0584:donfsi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Demography Of Northern Flying Squirrels Informs Ecosystem Management Of Western Interior Forests

Abstract: We studied northern flying squirrel (Glaucomys sabrinus) demography in the eastern Washington Cascade Range to test hypotheses about regional and local abundance patterns and to inform managers of the possible effects of fire and fuels management on flying squirrels. We quantified habitat characteristics and squirrel density, population trends, and demography in three typical forest cover types over a four-year period. We had 2034 captures of flying squirrels over 41 000 trap nights from 1997 through 2000 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
91
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(105 citation statements)
references
References 70 publications
8
91
5
Order By: Relevance
“…Presumably, the increase in tree diameters and heights, as well as understory coniferous structural diversity, in thinned stands at these densities may have provided sufficient canopy closure and concomitant food and cover (Sullivan et al 2010). Lehmkuhl et al (2006) found that a threshold of 55% canopy cover separated stands with low-and high-density populations of G. sabrinus.…”
Section: Glaucomys Sabrinusmentioning
confidence: 93%
See 1 more Smart Citation
“…Presumably, the increase in tree diameters and heights, as well as understory coniferous structural diversity, in thinned stands at these densities may have provided sufficient canopy closure and concomitant food and cover (Sullivan et al 2010). Lehmkuhl et al (2006) found that a threshold of 55% canopy cover separated stands with low-and high-density populations of G. sabrinus.…”
Section: Glaucomys Sabrinusmentioning
confidence: 93%
“…Although we did not evaluate response of hypogeous fungi to PCT, higher abundance of G. sabrinus in high-density stands might reflect a positive response of hypogeous fungi to thinning. Gomez et al (2005) and Lehmkuhl et al (2006) both concluded that the presence of hypogeous sporocarps may be more important for flying squirrels than forest structure. Rosenberg and Anthony (1992) suggested that food availability, predation, and competition with other species (e.g., Tamiasciurus, Smith 2012) may limit abundance of G. sabrinus more than struc- Fig.…”
Section: Glaucomys Sabrinusmentioning
confidence: 99%
“…Naturally recovering, structurally and compositionally diverse early successional ecosystems are biologically and functionally rich components of landscapes (Fontaine et al, 2009;Hutto, 1995;Kotliar et al, 2002;Smucker et al, 2005;Swanson et al, 2010), and they provide resources for many associated food webs (e.g., see Lehmkuhl, 2004;Lehmkuhl et al, 2006aLehmkuhl et al, , 2006b). Especially after severe fires, early successional forests are characterized by structural legacies (snags, logs, and remnant, mature live trees) with accompanying grassland, shrubland, woodland, or herbland dominance (Habeck, 1976;Hutto, 1995;Kotliar et al, 2002).…”
Section: Strategy 9: Creating and Maintaining Early Successional Forestsmentioning
confidence: 99%
“…Lehmkuhl et al (2006) hypothesized that silvicultural practices that retain less than 50% canopy cover would only support low-density populations of northern flying squirrels. Likewise, practices that sharply reduce supplies of coarse woody debris, which is associated with hypogeous fungi in northern flying squirrel diets (Carey et al 1999), may prevent this species from reaching the high densities characteristic of old forests (Carey 2000).…”
Section: Rodentsmentioning
confidence: 99%